2020
DOI: 10.1002/hpm.3093
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the choice of primary treatment at the community level among the middle‐aged and elderly in China

Abstract: Background: As China is still in the process of establishing the hierarchical medical system, people have full autonomy in choosing medical institutions when they need to see a doctor. The basic working of a hierarchical medical system involves four parts: primary treatment at the community level, two-way referral, a partition of emergency and chronic disease, and a joint effort among different healthcare facilities. This study examines factors associated with primary healthcare use in a middle-aged and elderl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…This echoed an earlier study that adjustments in health insurance reimbursement can promote patient visits to PCFs. [22] As medical expenses are one of the most determining factor in uencing health-seeking behaviors of Chinese patients, [9,20] studies observed that decreasing user fees for primary care and raising user fees for hospital ambulatory care increased primary care utilization. [15,46,47] Although the HMS policy in the Yinzhou model has been successfully implemented, many other pilots in China were not led by PCFs and PCPs remained peripheral within professional networks.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This echoed an earlier study that adjustments in health insurance reimbursement can promote patient visits to PCFs. [22] As medical expenses are one of the most determining factor in uencing health-seeking behaviors of Chinese patients, [9,20] studies observed that decreasing user fees for primary care and raising user fees for hospital ambulatory care increased primary care utilization. [15,46,47] Although the HMS policy in the Yinzhou model has been successfully implemented, many other pilots in China were not led by PCFs and PCPs remained peripheral within professional networks.…”
Section: Discussionmentioning
confidence: 99%
“…[1] Fragmentation of services negatively impacts patient satisfaction and further aggravated health inequity among residents. [10] To optimize residents' current healthcare-seeking behaviors and improve the e ciency of healthcare delivery, the Chinese government introduced the HMS policy package in 2014 [20]. Under this policy package, different levels of hospitals have a clear division of labor and coordinate to provide continuous, comprehensive and integrated care to individuals.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To improve the efficiency of healthcare delivery, the Chinese government introduced the HMS policy package in 2014 to alter patients’ healthcare-seeking behaviours and thus strengthen the role of primary care in delivering healthcare services ( Tao et al. , 2021 ).…”
Section: Introductionmentioning
confidence: 99%